Pangio bhujia, a new, peculiar species of miniature subterranean eel loach lacking dorsal and pelvic fins from India (Teleostei: Cobitidae) - Anoop, V.k.; Britz, Ralf; Arjun, C.p.; Dahanukar, Neelesh; Raghavan, Rajeev (Zootaxa, 2019)
A unique, new species of eel loach, Pangio bhujia, is described from Kerala, India. It is the first species of Pangio to be described from subterranean waters. It possesses several unusual characters including absence of both dorsal and pelvic fins, the presence of only 3 pectoral-fin rays, 6 anal-fin rays and a unique count of 38 precaudal + 24 caudal vertebrae.